Vacuna contra el COVID-19: ¿el ordenamiento jurídico peruano permite su aplicación obligatoria? - Valero Quispe, Christian Dennis (2021)
The health sector was not the only one affected by the COVID-19 pandemic, the rapid spread of this virus had an impact on education, the economy, work, tourism, among other sectors. This situation led various pharmaceutical laboratories around the world to initiate research to develop a vaccine. As a result of these international investigations, in the middle of 2020, a vaccination process was carried out; meanwhile, in Peru this process began at the beginning of 2021.  In this article, the author studies whether the Peruvian legal system allows the mandatory application of the COVID-19 vaccine. In order to achieve that, a balancing of rights was made between the individual freedom of those who do not wish to be vaccinated and public health. Additionally, he maintains that a measure such as restricting access to closed spaces must consider the principles of reasonableness and proportionality. In this way, it is concluded that it is not possible to coerce a person to take a medical treatment when they have not expressed their consent. However, it is possible to impose restrictions such as prohibiting access to means of transportation or admission to universities for people who are not vaccinated.